DISSEMINATION OF THE SI-PRAJA APPLICATION IN WAGE VILLAGE, TAMAN DISTRICT, SIDOARJO REGENCY THROUGH THE DIFFUSION OF INNOVATION PERSPECTIVE - Anggoro, Ken Bayu Yudho; Rachma Dewi, Putri Aisyiyah (The Commercium, 2024)
The rapid development of information technology has brought various innovations and ideas that facilitate access to various systems, including population administration and government document management. The implementation of e-government through stages of transformation, improvement, restructuring, revitalization, and updating development priorities and the smart city concept enables the public to obtain accurate information through city or district government applications, reducing the need to visit relevant agencies in person. Sidoarjo Regency, one of the regencies in East Java Province, strives to improve public services through the launch of the SI-PRAJA application. This application has been operational since 2021 and continues to evolve, encompassing various government agencies. Wage Village, part of Sidoarjo Regency, has adopted the SI-PRAJA application to enhance the efficiency and effectiveness of public services. This study examines the dissemination of the SI-PRAJA application in Wage Village using the perspective of innovation diffusion and evaluates its impact on user satisfaction. The study’s results indicate that the PIECES model variables significantly affect user satisfaction. The benefits of this research include academic contributions, improved quality of life for residents, and practical recommendations for village governments to enhance public administration services through digital technology.